TOXICITY TEST OF LIME PEEL EXTRACT (Citrus aurantifolia) USING THE BRINE SHRIMP LETHALITY TEST (BSLT) METHOD FOR DETECTION OF ANTI CANCER ACTIVITY - Khairunnisa, Indah; Widiastuti, Endang Linirin; Nurcahyani, Nuning (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2024)
Cancer is one of the major problems affecting the people of Indonesia and the world. Lack of public awareness for early detection causes a delay in diagnosis. One of the medicinal plants that are commonly found in Indonesia is lime (C. aurantifolia). In lime peel extract, there is essential oil composed of D-Limonene (38.94%), β-pinen (26.66%), α-terpineol (8.29%), and terpinen-4-ol (4.32%). These compounds are known to have strong effects as anti-cancer. This study used a completely randomized design (CRD) with 5 treatments and 5 repetitions, namely 0, 125, 150, 250, and 1000 ppm. The research methods used were phytochemical test, FTIR (Fourier-Transform Infrared Spectroscopy) analysis, and BSLT test. The probit value was analyzed using SPSS to obtain the LC50 value. Lime peel extract (C. aurantifolia) has an LC50 value of 331.533 ppm including the toxic category and has potential as an anti-cancer agent. Based on phytochemical and FTIR tests, lime peel (C. aurantifolia) contains alkaloid, flavonoid, and tannin compounds which are known to have antioxidant properties and can disrupt the balance of Reactive Oxygen Species (ROS) so as to trigger apoptosis of cancer cells.